The Influence Of The Human Organization Technology Fit Model On The Utilization Of Marine Operation System At Pt Pelabuhan Indonesia (Persero) Regional II - Muhammad Saiful Ludfi (Eduvest - Journal of Universal Studies, 2024)
The Marine Operating System (MOS) is an application that facilitates the planning, recording, and reporting of internal ship service information. The implementation of MOS at Tanjung Priok Port has shortened service times, reduced operational costs, and increased logistics productivity. However, the implementation of MOS faces various technical and non-technical challenges, including a lack of capacity in selecting or developing suitable information systems. PT Pelabuhan Indonesia (Persero) has made significant investments in the implementation of information systems but still faces challenges in system adoption. This study aims to investigate the use of the Human Organization Technology FIT (HOT FIT) analysis on the level of MOS utilization at PT Pelabuhan Indonesia (Persero) Regional II. The research objectives include testing and analyzing the quality of systems, information, and services regarding user satisfaction with MOS and its influence on net benefits. This research is expected to contribute theoretically to the development of business administration management science and serve as a reference for further research in the same field.